MODEL PEMBELAJARAN TGT BERBASIS GAMES TREASURE HUNT DALAM PEMBELAJARAN SEJARAH DI SMA - Gilar Wullida; Danu Eka Agustinova; Khofifah Nur Rahmah; Desy Jayanti; Griselda Afni Wulandari (STKIP Singkawang, 2025)
This study aims to describe the effect of implementing the Teams Games Tournament (TGT) learning model based on the Treasure Hunt game on students' learning motivation in history learning at the high school level. The study was conducted at Santo Bernadus High School, Pekalongan, in class X with 23 students consisting of 15 male students and 7 female students. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and questionnaires. The results of the study indicate that the TGT model based on Treasure Hunt is able to increase students' attention, involvement, and learning satisfaction. The presentation of history questions thematically and spread across various school locations creates an active, collaborative, and relevant learning atmosphere to students' lives. In addition, this approach is in accordance with the characteristics of adolescents who like challenges, exploration, and group work, thus contributing significantly to increasing learning motivation. This study recommends the TGT Treasure Hunt model as an innovative alternative in a more meaningful and enjoyable history learning strategy.